Karakteristik Morfologi, Perbedaan Jenis Kelamin, dan Pendugaan Umur Burung Weris (Gallirallus philippensis) di Minahasa, Sulawesi Utara (MORPHOLOGICAL CHARACTERISTICS, SEX DIFFERENCES, AND AGE ESTIMATION OF WERIS (GALLIRALLUS PHILIPPENSIS) FROM MINAHASA - Lambey, Lucia Johana; Noor, Ronny Rachman; Manalu, Wasmen; Duryadi, Dedy (Jurnal Veteriner, 2013)
This study aim  to observeb Gallirallus philippensis  similarities between different sites in Minahasa,to detect sexual dimorphism, and to estimate the bird age based on morphological characteristics.  A totalof 35 birds  were collected  from four locations i.e. Tondano, Papontolan, Ranoyapo, and Wusa in MinahasaNorth Sulawesi.   The result showed that there were no differences in the length  of beak, wing, and shankbetween  birds from  the different locations.  Moreover, based on the Principle Component Analysis (PCA)the bird’s shank and tail’s length were the main component.  Based on cluster analysis, the birds from fourlocations had a close similarities.  The male bird’s body weight, beak length, and beak width were largercomponent to the female’s.  The bird’s age could be best predicted by their iris colour,  beak colour, feather colourof the neck and the growth of the wing feathers, respectively.
Keywords: Gallirallus philippensis, morphological, sex, age